Gunshot wound to the chest with retained projectile in intraventricular septum. Issue 1 (January 2017) - Nash, Joshua; Yon, James Reidar; Kaminsky, Matthew; Smego, Douglas; Bokhari, Faran; Wall, Matthew J.
Abstract : Supplemental digital content is available in the text.